Pelatihan Pengelolaan Keuangan Berbasis Syariah Pada PKK Kabupaten Lumajang - Sri Abidah Suryaningsih; Clarashinta Canggih; Fira Nurafini; Moch. Khoirul Anwar; Maryam Bte Badrul Munir (Inspirasi Nusantara, 2023)
Lumajang is one of the areas in East Java, Indonesia, with a Muslim majority population. As Muslims, we must understand sharia rules, including how to manage sharia-based finance. Based on the results of the interviews, it was found that the majority of Lumajang District PKK cadres who are Muslim still do not optimally understand how to manage finances based on Islamic rules. Therefore, financial management training is needed from a sharia perspective to increase people's knowledge and abilities in managing finances according to Islamic rules to bring goodness to the world and the hereafter. Sharia-based financial management training is carried out through preparation, pre-test, training implementation, and post-test. The training results showed that the participant's understanding of sharia-based financial management increased from an average pre-test score of 71% and an average post-test score of 85%.